2010
DOI: 10.2220/biomedres.31.307
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of DMP1 and sclerostin in the epiphyseal trabecule and diaphyseal cortical bone of osteoprotegerin deficient mice

Abstract: In order to define the osteocytic function in accelerated bone remodeling, we examined the distribution of the osteocytic lacunar-canalicular system (OLCS) and osteocyte-secreting moleculesdentin matrix protein (DMP) 1 and sclerostin-in the epiphyses and cortical bones of osteoprotegerin deficient (OPG −/− ) mice. Silver impregnation visualized a well-arranged OLCS in the wild-type epiphyses and cortical bone, whereas OPG −/− mice had an irregular OLCS in the epiphyses, but well-arranged canaliculi in the cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
(51 reference statements)
3
18
0
Order By: Relevance
“…Enzyme histochemistry for tartrate-resistant acid phosphatase (TRAP), and immunohistochemistry for sclerostin, DMP-1, ER, osteopontin and RANKL Tartrate-resistant acid phosphatase (TRAP) was detected as previously described [36]; briefly, For immunohistochemistry, dewaxed paraffin sections were used for detection of sclerostin, DMP-1 and osteopontin as previously reported [30,37]. Endogenous peroxidase inhibition was conducted for all sections, and that was the first step in staining unless otherwise stated.…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzyme histochemistry for tartrate-resistant acid phosphatase (TRAP), and immunohistochemistry for sclerostin, DMP-1, ER, osteopontin and RANKL Tartrate-resistant acid phosphatase (TRAP) was detected as previously described [36]; briefly, For immunohistochemistry, dewaxed paraffin sections were used for detection of sclerostin, DMP-1 and osteopontin as previously reported [30,37]. Endogenous peroxidase inhibition was conducted for all sections, and that was the first step in staining unless otherwise stated.…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%
“…Complex meshwork of cement lines broadly distributed in the OVX mesial region appeared to be in agreement with fragmented osteocytic lacunar-canalicular system, referred to as OLCS, in the corresponding region. Masuki et al demonstrated fragmented OLCS by stimulated bone remodeling in mice with osteoprotegerin-depletion, and markedly-reduced synthesis of sclerostin [30]. In our study, the estrogen deficiency induced intense reactivity of RANKL in the mesial region of the alveolar bone, which may provide a similar milieu for osteoclastogenesis as that reported by Masuki et al Therefore, it seems reasonable that enhanced RANKL by estrogen deficiency would stimulate bone remodeling in the deeper mesial region, resulting in the fragmented OLCS, which inhibits secretion of sclerostin in osteocytes.…”
Section: Immunolocalization Of Er and Tunel-positive Osteocytes In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Immature, primary trabeculae contained randomly-oriented OLCS, revealing an intense tissue nonspecific alkaline phosphatase (TNAP)-reactivity, a hallmark of osteoblastic activities (3,26), on their surface. In contrast, secondary trabeculae constructed relatively-regular OLCS, and mature cortical bone demonstrated geometrically well-arrangement of OLCS, featuring TNAP-positive flattened, bone-lining osteoblasts (11,23,37). Normal bone remodeling is well known to make bone structure better strengthened and arranged so as to be resist against the mechanical stress, and by means of bone remodeling, the distribution of OLCS becomes progressively more regular as the individual grows.…”
Section: Methodsmentioning
confidence: 99%
“…Normal bone remodeling is well known to make bone structure better strengthened and arranged so as to be resist against the mechanical stress, and by means of bone remodeling, the distribution of OLCS becomes progressively more regular as the individual grows. Therefore, the biological activities of osteocytes seem to take place in bone metabolism by means of specific molecules-sclerostin and FGF23 (11,23,37). However, histological features of metaphyseal trabeculae and cortical bone chronologically change the area comprised by the last quarter of the metaphyseal trabeculae and the endosteal surfaces of the cortical bone.…”
Section: Methodsmentioning
confidence: 99%